Egg chemistry, production and consumption - Nys, Yves; Bain, Maureen; Van Immerseel, Filip (Woodhead Publishing in food science, technology, and nutrition ;, 2011)
Eggs are economical and of high nutritional value, yet can also be a source of foodborne disease. Understanding of the factors influencing egg quality has increased in recent years and new technologies to assure egg safety have been developed. Improving the safety and quality of eggs and egg products reviews recent research in these areas. Volume 1 focuses on egg chemistry, production and consumption. Part one sets the scene with information on egg production and consumption in certain countries. Part two then provides essential information on egg formation and chemistry. Factors that impact egg quality are the focus of part three. Chapters cover the role of poultry breeding, hen nutrition and laying environment, among other significant topics. Part four addresses organic and free range egg production, the impact of egg production on the environment and non-poultry eggs. A chapter on processed egg products completes the volume. With its distinguished editors and international team of contributors, Volume 1 of Improving the safety and quality of eggs and egg products is an essential reference for managers in the egg industry, professionals in the food industry using eggs as ingredients and all those with a research interest in the subject. Focuses on egg chemistry, production and consumption with reference to the factors than can impact egg qualityReviews recent research in the areas of disease, egg quality and the development of new technologies to assure egg safetyComprehensively covers organic, free-range and processed egg production.